Seseo, ceceo y distinción de /s y /Ɵ/: el caso de los políticos andaluces en Madrid - Cruz Ortiz, Rocío (El Colegio de México, 2019)
Until now, most of the studies of s/θ at the beginning of the syllable in Andalusia have focused on the behavior of these sibilants within its borders. However, few investigations have considered their outcome when coming into contact with a different system, such as the Castilian standard variety. This article aims to study the realization of s/θ in syllable-initial position in the speech of the Andalusian prime-ministers and ministers in Madrid between 1923 and 2011. The results show a convergence towards the national standard pronunciation, where the predominant solution is distinction, followed very far behind by seseo and, with an even smaller presence, by ceceo. The results show that the most significant factor of influence is the personal style of the speaker.